The Effectiveness of Health Administration in Improving Student Health through the School Health Program (UKS) - Safwa Salsabila, Suci; Apriliani, Aulia (Golden Ratio of Data in Summary, 2026)
The School Health Program (UKS) is a government initiative that plays a strategic role in promoting early health prevention and supporting long-term public health outcomes. This study examines the effectiveness of health administration in implementing the UKS program at elementary and secondary school levels, focusing on planning, organizing, implementation, and evaluation. A descriptive quantitative approach was employed using questionnaires completed by 30 respondents. The study highlights the significance of health administration as a crucial mechanism for translating policy objectives into effective operational practices within the school setting. The results show that the UKS program is generally well implemented, with 53.3% of respondents rating it as very good and 33.3% as good. UKS facilities and access to health personnel are considered adequate, and health services are responsive and student-friendly. These findings indicate that the foundational administrative structures and resources required to support UKS implementation are primarily in place at the school level. However, challenges remain, including irregular implementation of activities, limited student participation, and inconsistent evaluation. Collaboration with external health institutions also requires improvement. These constraints suggest that administrative effectiveness remains limited at the operational stage, particularly in ensuring continuity, stakeholder engagement, and the systematic monitoring of program activities. Overall, the UKS program has a positive influence on students’ knowledge, attitudes, and clean and healthy living behaviors (PHBS). This positive impact highlights the potential of school-based health programs to serve as effective entry points for health promotion among adolescents when supported by strong administrative management. Strengthening administrative management, evaluation systems, student engagement, and intersectoral coordination is crucial to enhancing the effectiveness and sustainability of the program and its contribution to broader public health objectives. The findings of this study provide practical implications for policymakers and school administrators in designing strategies to optimize UKS governance and maximize its role in improving student health outcomes.